Stability and instability of solitary waves of the fifth-order KdV equation: a numerical framework - Bridges, Thomas J.; Derks, Gianne; Gottwald, Georg (Physica. D, 2002)
The spectral problem associated with the linearization about solitary waves of the generalized fifth-order KdV equation is formulated in terms of the Evans function, a complex analytic function whose zeros correspond to eigenvalues. A numerical framework, based on a fast robust shooting algorithm on exterior algebra spaces is introduced. The complete algorithm has several new features, including a rigorous numerical algorithm for choosing starting values, a new method for numerical analytic continuation of starting vectors, the role of the Grassmannian G 2( C 5) in choosing the numerical integrator, and the role of the Hodge star operator for relating ⋀ 2( C 5) and ⋀ 3( C 5) and deducing a range of numerically computable forms for the Evans function. The algorithm is illustrated by computing the stability and instability of solitary waves of the fifth-order KdV equation with polynomial nonlinearity.